Beyond the classroom: online business as the lab for experiential learning - Budin, Husna; Mohamad Diah, Nurazzura (Human Resource Management Academic Research Society, 2023)
Information technology infrastructure is expanding at a rapid pace in this era to meet the demands of every industry and field, including education and economy. As such, by developing their skills and potential, students will have an entrepreneurial mindset that can assist them to prepare for the workforce. The objective of this paper is to examine how experiential learning in digital entrepreneurship helps to develop the entrepreneurial mindset among student entrepreneurs in higher learning institutions. This study used the qualitative method specifically in-depth interviews and participant observations. Using purposive sampling, 20 participants from selected fields of study were chosen. All interviews were transcribed and analysed using a thematic approach. The findings reveal that experiential learning in online business helped students to manage crises efficiently, increased their autonomy and authenticity as well as developed self-reflection habits. Through consistent practice, students can stimulate their creativity and become more critical of their circumstances too. This will help them to have new interpretations to direct their future actions. Experiential learning allows students to develop their entrepreneurial mindset and intentions, learn about people and their culture. Future graduates should participate in a range of experiential learning activities in online business that may aid in the development of their entrepreneurial mindset. In short, experiential learning is more than ever a practical approach in getting students to engage with real-world situations. It has an enormous impact on students' attitudes and abilities, making them more competitive graduates, particularly in the digital era